A comparative profitability analysis of transcatheter versus surgical aortic valve replacement in a high-volume French hospital - François Huchet; Jacques Chan-Peng; Fanny d'Acremont; Patrice Guerin; Gael Grimandi; Jean-Christian Roussel; Julien Plessis; Vincent Letocart; Thomas Senage; Thibaut Manigold (Health Economics Review, 2019)
Background: Current scientific guidelines have extended the indication for transcatheter aortic valve replacement (TAVR) to patients who present an intermediate risk for surgery and have been so far considered for conventional surgery. We previously demonstrated that the TAVR procedure generated profits despite elevated costs, but comparison with surgery has not been performed. The objective of this study was to assess the profitability of the TAVR procedure compared with conventional surgery in a high-volume French hospital. Consecutive patients eligible for transfemoral TAVR or surgical aortic valve replacement (SAVR) were included retrospectively in this single-centre study between September 2014 and December 2015. The primary endpoint was the profitability of each procedure (defined as the ratio between the profit and total revenues), calculated for each patient. Secondary composite endpoints included major adverse events in the 30 days following procedure and breakdown of costs. Results: Two hundred and thirty-eight patients were included in the TAVR group and 341 in the SAVR group. TAVR patients presented higher operative risk scores and more comorbidities. Compared with SAVR, TAVR was associated with higher profits ( exteuro2732 ± 1768 per patient vs. exteuro2177 ± 2437 per patient, P < 0.001) but also higher costs ( exteuro27,778 ± 4961 vs. exteuro17,813 ± 6071, P < 0.001) resulting in lower profitability (9.3 ± 5.7% vs. 11.7 ± 10.1%, P < 0.001). The price of the bioprosthesis represented 70% of the TAVR total cost. Conclusions: TAVR performed in carefully selected patients was associated with higher profits than SAVR, but also higher costs resulting in lower profitability.
Keywords: 330; Economical/cost-effectiveness; Aortic valve disease; percutaneous intervention; Cardiovascular diseases